PEMANFAATAN APLIKASI BENIME UNTUK PEMBELAJARAN MAHARAH KALAM DI MADRASAH ALIYAH NEGERI - Amrina, Amrina; Mudinillah, Adam; Husna, Kuntum Haviza (Universitas Muhammadiyah Makassar, 2023)
In this study, the researcher used a qualitative research method, which requires data that is in accordance with the original, in which the researcher used an interview with one of the teachers at Madrasah Aliyah Negri 2 Koto Baru Padang Panjang, making observations by descending To that location. Here the researchers conducted a study using the Benime application, the Benime application is one of the media that can help educators to create interesting teaching materials and has many features that can be used. The advantage of this Benime application is that this application has many features, its features include: There are stickers, text, backgrounds, moving hand animations, and the main menu is moving hand animations, helping educators in providing teaching materials in the form of videos, adding insight, and knowledge of educators or students, as well as giving an interesting impression, and providing motivation with their presence. Benime application-based learning videos. The benefit of this application is that it can help educators make a learning video, and also provide benefits to students in understanding a given material, and can have a positive impact on students by providing critical thinking about the material provided by educators. So that with the Benime application, it can facilitate the activities or activities of educators and students in learning maharah kalam.